PENINGKATAN TINGKAT KEPUASAN DOSEN TERHADAP KUALITAS PELAYANAN PELATIHAN JURNAL BERKUALITASMELALUI METODE SERVQUAL - Purnama, Adhy; Sailah, Ilah (Jurnal Manajemen, 2017)
This study aims to provide information on the level of satisfaction of trainees Journal service quality training quality and the most influential factor in the region Ko3f gpertis III. Methods of data collection in this study using the registration documentation (questionnaires), interviews and observations. Data were analyzed using descriptive analysis techniques servqual quantitative analysis method and Cartesian diagrams using SPSS 17. Based on the research results can be obtained gap (the gap value) of tangible dimension, realibility, responsivness, empathy, and assurance sequentially ie -1.69, -2.12, - 2:09, -2.04, and -1.75. Based on the analysis Cartesian diagram attributes into three main priorities for repair ie friendliness, attention and courtesy of the staff committee and their instructors, clear information about the facility and rules for participants, classroom facilities to support teaching and learning activities.